Understanding how PrEP is made successful: Implementation science needs an evidence-making approach - Anthony K. J. Smith; Kari Lancaster; Tim Rhodes; Martin Holt (Taylor & Francis Group, 2023)
After a decade of oral HIV pre-exposure prophylaxis (PrEP), the next generation of PrEP is being anticipated, including long-acting pills, injections, and implants. The unevenness of international PrEP implementation is increasingly recognised, with successful rollout in some settings and failure in others. There is a need to better understand conditions of PrEP implementation, and its localised (and sometimes unanticipated) effects. Implementation science explores how contexts and health systems shape the successful translation of health interventions. In this essay, we consider how PrEP is evolving and argue for an 'evidence-making' approach in relation to evidence and intervention translations. This approach emphasises how both interventions and their implementation contexts are co-constituted and evolve together. Unsettling the assumed universality of an intervention's effects and potential in relation to its implementation contexts helps to harness the localised possibilities for what PrEP might become. As the next generation of PrEP offers renewed promise, we must explore how PrEP is put to use and made to work in relation to its evolving situations. We urge implementation science to consider implementation processes as 'evidence-making events' in which evidence, intervention and context evolve together.